An analysis of milk fouling formed during heat treatment on a stainless steel surface with different degrees of roughness - Joanna Piepiórka-Stepuk; Katarzyna Tandecka; Marek Jakubowski (Czech Journal of Food Sciences, 2016)
Results of research on the effect of stainless steel (SS) surface roughness on the amount and microscopic structure of milk impurities, formed under the influence of high-temperature milk processing are presented. Three types of plates of different roughness were used in the study: Ra = 0.028 µm; Ra = 0.174 µm; Ra = 0.445 µm. The plates were immersed in raw milk and heated at 85-90°C for 30 min, imitating pasteurisation conditions. As a result of this action, a milk sediment difficult to remove was created. The structure of impurities was determined by the Confocal Scanning Laser Microscope CSLM method. The analysis of the microscopic structure of formed milk impurities enabled their classification into three types depending on their structure and way of their bonding to the surface. The research results suggested that the roughness plays a prominent role in the level of fouling and probably in cleaning effectiveness.